Physiological and metabolic responses of Scenedesmus quadricauda (Chlorophyceae) to nickel toxicity and warming - Yong, Wai Kuan; Sim, Kae Shin; Poong, Sze Wan; Wei, Dong; Phang, Siew Moi; Lim, Phaik Eem (Springer Verlag (Germany), 2019)
An ecologically important tropical freshwater microalga, Scenedesmus quadricauda, was exposed to Ni toxicity under two temperature regimes, 25 and 35 °C to investigate the interactive effects of warming and different Ni concentrations (0.1, 1.0 and 10.0 ppm). The stress responses were assessed from the growth, photosynthesis, reactive oxygen species (ROS) generation and metabolomics aspects to understand the effects at both the physiological and biochemical levels. The results showed that the cell densities of the cultures were higher at 35 °C compared to 25 °C, but decreased with increasing Ni concentrations at 35 °C. In terms of photosynthetic efficiency, the maximum quantum yield of photosystem II (Fv/Fm) of S. quadricauda remained consistent across different conditions. Nickel concentration at 10.0 ppm affected the maximum rate of relative electron transport (rETRm) and saturation irradiance for electron transport (Ek) in photosynthesis. At 25 °C, the increase of non-photochemical quenching (NPQ) values in cells exposed to 10.0 ppm Ni might indicate the onset of thermal dissipation process as a self-protection mechanism against Ni toxicity. The combination of warming and Ni toxicity induced a strong oxidative stress response in the cells. The ROS level increased significantly by 40% after exposure to 10.0 ppm of Ni at 35 °C. The amount of Ni accumulated in the biomass was higher at 25 °C compared to 35 °C. Based on the metabolic profile, temperature contributed the most significant differentiation among the samples compared to Ni treatment and the interaction between the two factors. Amino acids, sugars and organic acids were significantly regulated by the combined factors to restore homeostasis. The most affected pathways include sulphur, amino acids, and nitrogen metabolisms. Overall, the results suggest that the inhibitory effect of Ni was lower at 35 °C compared to 25 °C probably due to lower metal uptake and primary metabolism restructuring. The ability of S. quadricauda to accumulate substantial amount of Ni and thrive at 35 °C suggests the potential use of this strain for phycoremediation and outdoor wastewater treatment.